Cultivating Interest in Reading and Writing Through Short Stories Using Picture Story Books in Elementary School Students in Temiyang Village, Kroya District, Indramayu Regency - Nurmaelinda; Jesicha nais (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to improve the reading and writing interests of elementary school students in Temiyang Village through a community service program. Based on observations, students' reading abilities and interests at Temiyang 2 Public Elementary School are still low, students are easily bored with conventional learning methods, lack of parental attention, and the dominance of online games are the main problems. Referring to the 2006 KTSP, improving communication skills in Indonesian, both oral and written, and fostering an appreciation for literature are important goals. Reading, as one of the four language skills (listening, speaking, reading, writing), has been identified as having a significant influence on the development of students' potential, reasoning ability, concentration, and achievement. This program uses lecture, discussion, and practice methods, utilizing digital learning media such as storybooks and PowerPoint applications. Storybooks, according to Rothlein and Meinbach (1991), are effective in improving language skills, developing memory, introducing new things, and arousing children's interest in reading. The program targets students in grades 1-6 at Temiyang 2 Public Elementary School. The activity was carried out on July 15, 2024. Data collection was carried out through pretests and posttests, as well as interviews. Data analysis using the N-Gain test showed a significant increase in students' comprehension of the reading material. The average N-Gain score of 0.82 (81.74%) indicated a high level of program effectiveness. Despite obstacles, such as some students still having difficulty reading and requiring more time, the enthusiasm of the fourth-grade students contributed to the smooth running of the program. The program resulted in published reports and an increase in students' imagination and creativity in reading by approximately 80%. Students also experienced enjoyment and a lack of boredom while learning Indonesian. This program is expected to serve as a foundation for schools and teachers to continue developing literacy programs that are engaging and relevant to students' needs.